Picture Exchange Communication System (PECS) to Enhance the Expressive Language Skills of Children with Developmental Language Disorders - Dicky Listin Quarta (UPT Publikasi Ilmiah UNISBA, 2024)
A B S T R A C T Expressive language disorder is a child's inability to express the words and sentences they want to say in accordance with the proper language order. As a result, the subject has no friends at school, has difficulty communicating, is unable to articulate his wishes, and in the end often fights with his friends. This study aims to determine the role of Picture Exchange Communication System (PECS) in improving expressive language skills in children with expressive language disorders. The subject is a boy aged 3 years and 6 months who was diagnosed with expressive language disorder. This study applies an experimental methodology and a single-subject research design. PECS was given to children for 6 meeting sessions. The results of this study were analyzed using descriptive analysis which showed an increase in the subject's expressive language skills after the intervention. Keywords : Language development disorders, expressive language skills, Picture Exchange Communication System